2020
DOI: 10.1007/s00401-020-02179-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced axonal response of mitochondria to demyelination offers neuroprotection: implications for multiple sclerosis

Abstract: Axonal loss is the key pathological substrate of neurological disability in demyelinating disorders, including multiple sclerosis (MS). However, the consequences of demyelination on neuronal and axonal biology are poorly understood. The abundance of mitochondria in demyelinated axons in MS raises the possibility that increased mitochondrial content serves as a compensatory response to demyelination. Here, we show that upon demyelination mitochondria move from the neuronal cell body to the demyelinated axon, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 87 publications
(133 reference statements)
8
81
2
1
Order By: Relevance
“…The successful manipulation of a key pathway involved in mitochondrial energy metabolism adds to the emerging spinal cord injury literature that has shown that restoring cellular energetics and axonal transport promotes axonal outgrowth and regeneration [ 42 ]. Our data suggest that targeting this tractable pathway may thus also be highly relevant to neurodegeneration [ 56 , 75 ], accepting the possibility of there being other competing mechanisms driving the dysfunctional axonal homeostasis observed in C9orf72 MNs.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The successful manipulation of a key pathway involved in mitochondrial energy metabolism adds to the emerging spinal cord injury literature that has shown that restoring cellular energetics and axonal transport promotes axonal outgrowth and regeneration [ 42 ]. Our data suggest that targeting this tractable pathway may thus also be highly relevant to neurodegeneration [ 56 , 75 ], accepting the possibility of there being other competing mechanisms driving the dysfunctional axonal homeostasis observed in C9orf72 MNs.…”
Section: Discussionmentioning
confidence: 84%
“…Briefly, FLAG-PGC1α-6xHIS (originated from Addgene [67637]) and P2A-eGFP (originated from pDONR-P2A-eGFP), were shuttled into a lentiviral backbone pLenti6-cppt-delta CMV-DEST-opre, to generate a FLAG-PGC1α-6xHIS-P2A-eGFP lentiviral construct. PGC1α overexpression lentivirus was generated as previously described [ 63 , 76 ] and transduced as previously described by our group [ 56 ] in human iPSC-derived MNs at a multiplicity of infection (MOI) of 10. This achieved a mean transduction efficiency of circa 70% MNs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to exchange axonal Na + for extracellular K + will activate the Na + /Ca 2+ exchanger and dramatically increase axoplasmic concentrations of Ca 2+ , which can induce a virtual axonal hypoxia and cause axonal degeneration [ 91 ]. While the axon eventually compensates for this increased energy demand by increasing the volume of axoplasmic mitochondria [ 92 95 ], it may be initially vulnerable to the increased ionic exchange associated with loss of myelin. We consider dendritic silencing to be a neuroprotective response that reduces axonal conduction and helps prevent degeneration of demyelinated axons.…”
Section: Discussionmentioning
confidence: 99%
“…More recently Licht‐Mayer et al used an axonal guidance device as a model of demyelination using a co‐culture of neurons with oligodendrocyte precursor cells and inducing demyelination by exposing the axonal compartment to lysolecithin, (which is similarly used in animal models of demyelination). Licht‐Mayer et al used this system to help uncover a novel process in which mitochondria move from the neuronal cell body to the demyelinated axon, increasing axonal mitochondrial content, and that enhancing this process protects acutely demyelinated axons from degeneration (Licht‐Mayer et al., 2020). Understanding such mechanisms of protection may have profound future implications for treatment of MS.…”
Section: Microfluidic Models Of Neurological Diseasesmentioning
confidence: 99%